2022
DOI: 10.1111/iej.13870
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two different root canal sealers on treatment outcome and post‐obturation pain in single‐visit root canal treatment: A prospective randomized clinical trial

Abstract: Aim This randomized clinical trial aimed to evaluate and compare the effect of mineral trioxide aggregate (MTA)‐based bioceramic‐ and resin‐based sealers on the incidence and intensity of post‐obturation pain and treatment outcome in asymptomatic vital molar teeth in single‐visit root canal treatment. Methodology One hundred asymptomatic mandibular molar teeth with vital pulp were randomly assigned into two groups according to the sealer used: MTA Fillapex or AH Plus sealer. WaveOne Gold instruments were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…In prospective studies, similar success rates were reported for the single cone technique using BioRoot RCS and warm vertical compaction technique using an epoxy resin‐based sealer 165 or a zinc oxide‐eugenol sealer 167 . According to a randomized clinical trial, MTA Fillapex showed a similar success rate to an epoxy resin‐based sealer at a 2‐year follow‐up when used with a single cone technique 166 …”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…In prospective studies, similar success rates were reported for the single cone technique using BioRoot RCS and warm vertical compaction technique using an epoxy resin‐based sealer 165 or a zinc oxide‐eugenol sealer 167 . According to a randomized clinical trial, MTA Fillapex showed a similar success rate to an epoxy resin‐based sealer at a 2‐year follow‐up when used with a single cone technique 166 …”
Section: Introductionmentioning
confidence: 58%
“…163 One of the most commonly used rootfilling techniques with CSSs in clinical studies was the single cone technique. [164][165][166] According to a retrospective study using iRoot SP sealer with a single cone technique, the success rate was 96.8% and iRoot SP extrusion had no adverse effect on the treatment outcome. 164 In prospective studies, similar success rates were reported for the single cone technique using BioRoot RCS and warm vertical compaction technique using an epoxy resin-based sealer 165 or a zinc oxide-eugenol sealer.…”
Section: Root Canal Sealermentioning
confidence: 99%
See 2 more Smart Citations
“…As the authors have stated, there are multiple factors that can affect postoperative pain such as; debris extrusion, root canal preparation technique, root canal sealer type and root canal filling technique, which are already mentioned in the published article (Gondim Jr et al, 2010;Ng et al, 2004;Wang et al, 2010). These factors have been the focus of our group for many years (Coşar et al, 2022;Kandemir Demirci et al, 2021;Kandemir Demirci & Çalışkan, 2016;Miçooğulları Kurt & Çalışkan, 2018;Yaylali et al, 2018).…”
Section: Response To Editormentioning
confidence: 92%